(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Syzygium cumini (L.) skeels (Family: Myrtaceae) is a renowned medicinal plant traditionally used in various diseases and available in Bangladesh. This investigation was aimed to explore whether this plant has any potential antioxidant, antibacterial, and analgesic effects of methanolic extracts of S. cumini (leaves and bark). Quantitative determination of methanolic extracts of leaves and bark found the total phenolic contents as 199.11 mg GAE/g DW and 204.03 mg GAE/g DW, respectively. The leaves extract possessed mild antibacterial activity (leaves: 7.00 mm at 1 mg/disc, 9.15 mm at 5 mg/disc) against two different bacteria at different concentration whereas the bark extract showed no effect. A significant writhing (leaves: 23.17 ± 1.80, p≤0.001; bark: 24.33 ± 1.15, p≤0.001) and licking effects (leaves: 8.17 ± 1.49 sec, p≤0.05; bark: 9.08 ± 1.96 sec, p≤0.05) were found at 400 mg/kg of leaves and bark extracts of this plant which is very close to standard drugs mentioned in the tables. Results of this study demonstrated that methanolic extracts of S. cumini leaf and bark possessed significant antioxidant, analgesic, and mild antibacterial like activities which tend to suggest medicinal aspects. Dhaka Univ. J. Pharm. Sci. 21(1): 15-24, 2022 (June)